Gestión financiera en la Municipalidad Provincial de Maynas periodo 2023 - Vasquez Zevallos, Johana del Carmen (2025)
The objective of this research was to determine how Financial Management was in the Provincial Municipality of Maynas in the period 2023, with a type of quantitative research and a descriptive non-experimental design, it included a population of 25 workers from the Provincial Municipality of Maynas, The survey was used as a data collection instrument; The research concluded that financial management in the Provincial Municipality of Maynas during 2023 was positive and efficient, with a high percentage of respondents (92%) indicating that the Municipality adequately manages the public budget, reflecting correct planning and execution of financial resources, in addition to the fact that the financial programming in the Provincial Municipality of Maynas was effective and well structured. 76% of those surveyed consider that the payment plan is executed constantly, which demonstrates adequate planning and the alignment of resources with the established goals. It was also determined that financial control in the Municipality was generally well perceived with 76% of respondents indicating that financial controls are performed consistently. However, a significant percentage (36%) suggest that financial control is carried out only "almost always" or "some of the time", indicating that the frequency and communication of these controls could be improved.